Atrial Fibrillation and Cancer - Hajjar, Ludhmila Abrahao; Fonseca, Silvia Moulin Ribeiro; Machado, Theuran Inahja Vicente (Frontiers in Cardiovascular Medicine, 2021)
Cancer patients have a higher risk of atrial fibrillation (AF) than general population, The pathophysiology mecanisms involves the pro inflammatory status of immune system in these patients and the exacerbated inflammatory response to cancer treatment and surgeries. Adequate management and prophylaxis for its occurrence are important and reduce morbidity and mortality in this population. There is a challange in AF related to cancer to predict thromboembolic and bleeding risk in these patients, once standard stroke and hemorragic prediction scores are not validated for them. It is used CHA2DS2-VASc and HAS-BLED scores, the same as used in general population. In this review, we demonstrate correlataded mechanisms to occurrance AF in cancer patients as well as therapeutic challenges in this population .